From Staple Crop to Strategic Bioeconomy: Policy Pathways for Unlocking Indonesia's Cassava Value Chain and Rural Welfare through Lessons from Thailand - Loso Judijanto (Nomico, 2026)
Cassava is simultaneously a food crop, industrial starch feedstock, source of animal feed, renewable-energy feedstock, and a biomass platform for a circular bioeconomy. Yet Indonesia captures only a fraction of this multifunctional value. This article develops a qualitative literature review of recent peer-reviewed research, complemented by official statistics, to examine why Indonesia's cassava economy remains below its potential and what policy architecture could raise farmer welfare and national value added. The review is narrative and interpretive rather than systematic: literature published mainly since 2020 was purposively and iteratively assembled across agronomy, plant health, food science, value-chain governance, industrial processing, bioenergy, biomaterials, and rural development. The synthesis finds that Indonesia's central constraint is not simply insufficient production. It is a coordination problem linking planting-material quality, farm productivity, postharvest logistics, starch-based price formation, farmer bargaining power, factory utilisation, technological upgrading, market development, and environmental management. Thailand demonstrates the benefits of long-run breeding investment, starch-oriented production, dense processing networks, diversified product markets, and stronger industry coordination, but its experience also shows that contract farming and industrial concentration do not automatically guarantee equitable outcomes. The article proposes seven mutually reinforcing policy pillars: clean seed systems; productivity and finance; transparent market governance; territorial industrial clusters; downstream upgrading; resilient supply coordination; and circular biorefinery development. The policy objective should be to increase total value created per hectare and ensure that smallholders capture a larger, more stable share of that value